2015
DOI: 10.1039/c5ra06892d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CO2 on the CVD synthesis of carbon nanomaterials using fly ash as a catalyst

Abstract: The efficient use of fly ash is a worldwide issue due to its high production and harmful effects on the environment. In this work the synthesis of carbon nanomaterials (CNMs) via the chemical vapour deposition (CVD) method, using fly ash as a catalyst and CO 2 as an alternate carbon source, was investigated. Here CO 2 was employed in three different ways: (1) as a sole carbon source, (2) as an additive to C 2 H 2 and (3) as a carbon source prior to the reaction of C 2 H 2 with fly ash. SEM, TEM and laser Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…Most zeolites are periodic framework compounds of aluminium silicates formed by interconnected SiO 4 and AlO 4 tetrahedrons [30]. Owing to the crystalline nature and the abundant AlO 4 sites, zeolites possess well-defined distribution of pore size and outstanding cation-exchange capacity, enabling extensive industrial applications as adsorbents [31][32][33][34], catalysts [35], catalyst supports [36,37] and cation-exchange materials [38][39][40][41][42]. Zeolites are conventionally synthesized with sodium silicate and aluminate through hydrothermal crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Most zeolites are periodic framework compounds of aluminium silicates formed by interconnected SiO 4 and AlO 4 tetrahedrons [30]. Owing to the crystalline nature and the abundant AlO 4 sites, zeolites possess well-defined distribution of pore size and outstanding cation-exchange capacity, enabling extensive industrial applications as adsorbents [31][32][33][34], catalysts [35], catalyst supports [36,37] and cation-exchange materials [38][39][40][41][42]. Zeolites are conventionally synthesized with sodium silicate and aluminate through hydrothermal crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies showed that both the diameter and the thickness distribution range increase drastically with increase in temperature. 30 This is because metal catalyst particles tend to sinter or agglomerate such that they catalyse the synthesis of thicker CNFs. This is coupled by temperature enhanced decomposition of C 2 H 2 and thus more carbon available for knitting the carbon matrix of the CNFs.…”
Section: Pxrd and Epma Analyses Of Catalystmentioning
confidence: 99%
“…7,20,[24][25][26] furthermore, this study is a parametric study that reports on some of the factors that have been reported to inuence the growth of carbon nanomaterials using a CVD setup. [27][28][29][30][31]…”
Section: Introductionmentioning
confidence: 99%
“…12 Likewise we have shown that the yields of CNFs could be enhanced by pre-treating CFA with CO 2 before the introduction of C 2 H 2 and H 2 . 13 Saudi Arabian and Japanese CFA have also been used to synthesize undoped CNTs. 14,15 Similarly, Salah et al have optimised the synthesis parameters (temperature, gas pressure, growth times, and gas ow rates for the decomposition of C 2 H 2 in the presence of H 2 ) for the growth of undoped MWCNTs on carbon rich CFA by low pressure chemical vapour deposition (LPCVD).…”
Section: Introductionmentioning
confidence: 99%